Advancements in nanotherapeutics for Alzheimer's disease: current perspectives. (15th July 2019) - Harilal, Seetha; Jose, Jobin; Parambi, Della Grace Thomas; Kumar, Rajesh; Mathew, Githa Elizabeth; Uddin, Md Sahab; Kim, Hoon; Mathew, Bijo
Abstract: Objectives: Considerable progress has been made in the treatment of Alzheimer's disease (AD), but all available strategies focus on alleviating symptoms rather than curing, which means that AD is viewed as an unresolvable neurodegenerative disease. Nanotechnological applications offer an alternative platform for the treatment of neurodegenerative diseases. This review aims to summarize the recent nanomedicine and nanotechnology developments for the treatment of AD. Key findings: A plethora of nanocarriers and nanoparticle prodrugs have been reported to have negligible cytotoxicity in animal models, and these developments have revealed new opportunities for development of new classes of potent drug formulations for AD. Different nanotechnology-based approaches such as polymers, emulsions, lipo-carriers, solid lipid carriers, carbon nanotubes and metal-based carriers have been developed over the past decade, and they have been focusing on both neuroprotective and neurogenerative techniques to treat AD. Studies also reveal that nanotechnological approaches can aid in early diagnosis of AD and enhance therapeutic efficacy and bioavailability. Summary: Notably, the drugs used conventionally to target the central nervous system have limitations that include an inability to cross the 'blood–brain barrier' or the 'blood–cerebrospinal fluid barrier' effectively and high drug efflux due to the activity of P-glycoprotein, but these limitations can be successfully overcome when nanocarriers are used for targeted drug delivery in AD.